Complete identity and expression of StfZ, the cis-antisense RNA to the mRNA of the cell division gene ftsZ, in Escherichia coli - Anand, Deepak; Jakkala, Kishor; Nair, Rashmi Ravindran; Sharan, Deepti; Pradhan, Atul; Mukkayyan, Nagaraja; Ajitkumar, Parthasarathi (Frontiers in Microbiology, 2022)
Bacteria regulate FtsZ protein levels through transcriptional and translational mechanisms for proper cell division. A cis-antisense RNA, StfZ, produced from the ftsA-ftsZ intergenic region, was proposed to regulate FtsZ level in Escherichia coli. However, its structural identity remained unknown. In the present study, we determined the complete sequence of StfZ, identified the isoforms and its promoters. We find that under native physiological conditions, StfZ is expressed at a 1:6 ratio of StfZ:ftsZ mRNA at all growth phases from three promoters as three isoforms of 366 nt, 474 nt, and 552 nt RNAs. Overexpression of StfZ reduces FtsZ protein level, increases cell length, and blocks cell division without affecting the ftsZ mRNA stability. We did not find differential expression of StfZ under the stress conditions of heat shock, cold shock, or oxidative stress, or at any growth phase. These data indicated that the cis-encoded StfZ antisense RNA to ftsZ mRNA may be involved in the fine tuning of ftsZ mRNA levels available for translation as per the growth-phase-specific requirement at all phases of growth and cell division.